Terracottas from the Votive Deposit of the Thesmophorion at Gortyn (Hatzidakis Excavation, 1909-1910) - Kyrimi, Maria; Mikrakis, Manolis (O T I V M, 2024)
The unpublished votive figurines from the thesmophorion of Gortyn in southern Crete discussed in this preliminary paper include piglet-holding female votaries, women carrying baskets or water jars, women holding flowers or fruits, enthroned female figures, nude or clothed men and male adolescents, Daedalic-type figurines and relief plaques, a large Zeus figurine, and various Isis, Aphrodite and Nike types. These votives point to a much-frequented sanctuary dedicated to the female cult of Demeter and Kore/Persephone and, in particular, to marriage- or death-related rites of passage for young girls. In terms of date, the material is predominantly Hellenistic, but Geometric, Archaic and Classical examples can also be identified. From the study of these terracottas, interesting observations can be made regarding artistic production, cult and votive practices, religious beliefs and social organization in Classical and Hellenistic Crete.